URGENSI PENERAPAN METODE PAIKEM BAGI GURU DALAM MENINGKATKAN MUTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Mohammad Adnan (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2017)
Human learning process lasted until the end of life (long life education). School is one institution that runs the process. In essence learning is a process of transactional communication between teachers and students where in the process is mutual. Transactional communication is a form of communication that can be accepted, understood, and agreed by the parties involved in the learning process. Learning is the procedure and method pursued by the teacher to make it easy for learners to actively learn in order to achieve the learning objectives. However, the process does not run easily there is one method that must be taken when in the learning process there are problems. And of course in public schools are a lot of problems is the subject of PAI, in addition to the hours of very minimal subjects that is only one meeting in a week. The second problem is that teachers are also required to have a good ability to determine the condition. Therefore it is important here to be able to apply one method of learning that is PAIKEM. Because this method will help the teacher to create an excellent learning process